Support for smallholder farmers through Islamic instruments: The case of Bangladesh and lessons for Nigeria. Issue 2 (2019) - Hossain, Ishrat; Muhammad, Aliyu Dahiru; Jibril, Binta Tijjani; Kaitibie, Simeon
Abstract : Purpose: In societies with strong presence of Islam, Islamic instruments with more scope for fairness and equity can be innovatively harnessed to play an increasing role in the development process and poverty alleviation schemes. Poor smallholder farmers dominate agricultural production in many developing countries and contribute a significant portion of global food production. This paper aims to develop a scheme to improve poor smallholder farmers' vulnerable financial situation through the application of Zakah and Salam contract, using Bangladesh as a case study. Secondary goals are to show the effect of the scheme on food security and relevance to Nigeria. Design/methodology/approach: The authors explore the existing traditional modes of financing available to poor smallholders, identify their challenges and propose an appropriate Islamic financing scheme. Findings: With the Zakah -based Salam forward contract, the proposed scheme would procure food through Institutional Demand to offer interest free financing, fair price and access to new marketing channels and reduce income uncertainty for the rural smallholders. The discussions indicate that the local food security will be enhanced through incentivized farming activities and disbursement of food from the food bank to the Zakah -eligible food insecure local people. Research limitations/implications: This proposal brings forth a potentially powerful idea that needs further empirical validation. Originality/value: The religion-based Institutional Demand initiative to promote smallholder agricultural development and social protection is a novel one. The attempt to apply the framework to Nigeria context shows the potential of the framework to generalize for other Muslim developing countries with similar characteristics, especially the poorer agriculture-based countries.